PERAN AKUNTAN FORENSIK DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI - Riski Nilam Sari; Erna Wahyusetianingsih; Hawa Azzah Fauziah; Gunawan Aji (Kampus Akademik Publiser, 2024)
Forensic accounting plays an important role in eradicating criminal acts of corruption by providing in-depth investigative techniques and methods to identify, analyze and uncover corrupt practices. Through a comprehensive analytical approach, forensic accounting enables uncovering illegal activities that are often hidden in complex financial records. Professionals in this field use their skills to detect fraud, data manipulation, and embezzlement of funds, as well as to collect evidence that can be used in legal proceedings. Forensic accounting not only helps in identifying perpetrators of criminal acts of corruption, but also in recovering stolen assets and preventing corruption in the future through recommendations for improving the internal control system. Thus, forensic accounting is a crucial tool in supporting transparency and accountability in the public and private sectors, as well as in creating a cleaner and corruption-free environment. This article aims to explore the role of forensic accounting in eradicating criminal acts of corruption, including the methods used, its use in corruption investigations and its benefits in the judicial process.